Draving Up a Budget Using The Activity Based Budgeting Methodology Through The Simulation Of Processes - Dita Janíková (Kvalita Inovácia Prosperita, 2011)
This paper deals with a connection between financial and quality management systems. These departments only rarely cooperate on projects, which could be a loss, because this connection has many improvement opportunities. The author shows through the simple example of catering deliveries a possible procedure of how to reach a more realistic evaluation of production costs for each product and how to connect budgeting and process analysis.